Analisis Terhadap Kesejahteraan Ekonomi Pedagang Pakaian Impor Bekas (Thrift) Melalui Media Sosial di Kota Medan - Nurul Aflah Harahap; Muhammad Yafiz; Budi Hariyanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the economic welfare of used imported clothing traders (Thrift) in Medan City. A qualitative descriptive method was used. Information was obtained through observation and conversations with used imported clothing traders (thrift) in Medan City. The research findings show that the digitalization of trade through social media has had a positive impact on the economic welfare of used imported clothing traders in Medan City. With wider access through social media, traders can reach more potential customers, both within and outside the Medan area. This can increase sales and profits for traders.